Mechanistic insights into the structure-based design of a CspZ-targeting Lyme disease vaccine - Kalvis Brangulis; Jill Malfetano; Ashley L. Marcinkiewicz; Alan Wang; Yi-Lin Chen; Jungsoon Lee; Zhuyun Liu; Xiuli Yang; Ulrich Strych; Dagnija Tupina; Inara Akopjana; Maria-Elena Bottazzi; et al. (Nature Communications)
Abstract Borrelia burgdorferi (Bb) causes Lyme disease (LD), one of the most common vector-borne diseases in the Northern Hemisphere. Here, we solve the crystal structure of a mutated Bb vaccine antigen, CspZ-YA that lacks the ability to bind to host complement factor H (FH). We generate point mutants of CspZ-YA and identify CspZ-YAI183Y and CspZ-YAC187S to trigger more robust bactericidal responses. Compared to CspZ-YA, these CspZ-YA mutants require a lower immunization frequency to protect mice from LD-associated inflammation and bacterial colonization. Antigenicity of wild-type and mutant CspZ-YA proteins are similar, as measured using sera from infected people or immunized female mice. Structural comparison of CspZ-YA with CspZ-YAI183Y and CspZ-YAC187S shows enhanced interactions of two helices adjacent to the FH-binding sites in the mutants, consistent with their elevated thermostability. In line with these findings, protective CspZ-YA monoclonal antibodies show increased binding to CspZ-YA at a physiological temperature (37 °C). In summary, this proof-of-concept study applies structural vaccinology to enhance intramolecular interactions for the long-term stability of a Bb antigen while maintaining its protective epitopes, thus promoting LD vaccine development.